2018
DOI: 10.1007/s00425-018-2911-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in steroidal saponins biosynthesis and in vitro production

Abstract: Main conclusion Steroidal saponins exhibited numerous pharmacological activities due to the modification of their backbone by different cytochrome P450s (P450) and UDP glycosyltransferases (UGTs). Plant-derived steroidal saponins are not sufficient for utilizing them for commercial purpose so in vitro production of saponin by tissue culture, root culture, embryo culture, etc, is necessary for its large-scale production.Saponin glycosides are the important class of plant secondary metabolites, which consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 333 publications
(115 reference statements)
2
52
0
4
Order By: Relevance
“…The presence of the glycosaponins in the plant has indicated that medicinal herb possesses hemolytic activity (Okwu and Okwu, 2004). Scientific studies have shown that saponins exhibit anti-microbial, anti-tussive, immunomodulation and anti-diabetic properties (Upadhyay et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the glycosaponins in the plant has indicated that medicinal herb possesses hemolytic activity (Okwu and Okwu, 2004). Scientific studies have shown that saponins exhibit anti-microbial, anti-tussive, immunomodulation and anti-diabetic properties (Upadhyay et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The fungal pathogens are suggested to survive the effect of active compounds (for instance, azole) due to the ability to decrease the accumulation of these compounds by different defense mechanisms [61]. Both Papadopoulou et al [62] and Upadhyay et al [63], indicated the potential antifungal effect of saponins.…”
Section: Resultsmentioning
confidence: 99%
“…Steroidal saponins are classi ed into two subfamilies, spirostanol type saponins and furostanol type saponins [35], there are furostanol and corresponding spirostanol type compounds simultaneously in plants [36], and furostanol saponins can be converted into spirostanol form when catalyzing by furostanol glycoside 26-O-β-glucosidase [37,38].…”
Section: Discussionmentioning
confidence: 99%